2014
DOI: 10.3346/jkms.2014.29.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Central Lymph Node Metastasis Is an Important Prognostic Factor in Patients with Papillary Thyroid Microcarcinoma

Abstract: Papillary thyroid microcarcinoma (PTMC) has been increasing, without a consensus for the management of this condition. In the present study, we analyzed the clinicopathological features of patients with PTMC to examine the impact of initial therapy and establish appropriate treatment. A total of 2,018 patients with PTMC were enrolled at a single university hospital. Of them, 1,245 patients (61.8%) underwent total thyroidectomy, and 1,838 patients (91.3%) underwent central lymph node (LN) dissection. Five-and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 28 publications
2
49
2
3
Order By: Relevance
“…Papillary thyroid microcarcinoma (PTMC), which is defined as a papillary carcinoma with the dimensions equal to or <1.0 cm, according to the World Health Organization classification (4), accounts for 6–35% of thyroid carcinoma and 35.7–61.5% of papillary thyroid carcinoma (PTC) (510). PTMC is considered with favorable biological features and good long-term prognosis, as the 10-year disease-specific survival of 99.5% (11).…”
Section: Introductionmentioning
confidence: 99%
“…Papillary thyroid microcarcinoma (PTMC), which is defined as a papillary carcinoma with the dimensions equal to or <1.0 cm, according to the World Health Organization classification (4), accounts for 6–35% of thyroid carcinoma and 35.7–61.5% of papillary thyroid carcinoma (PTC) (510). PTMC is considered with favorable biological features and good long-term prognosis, as the 10-year disease-specific survival of 99.5% (11).…”
Section: Introductionmentioning
confidence: 99%
“…Besides providing objective information about LN status, CLND has also value to reduce postoperative Tg levels and local recurrence rates. 10,11 Secondary benefit of pCLND would be minimizing patients' anxiety about a secondary operation. 2 Add to this the low accuracy of preoperative diagnostic tools in identifying nodal involvement, led several authors to consider CLND especially when dealing with recurrent disease.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown a higher risk of recurrence in the case of family aggregation of PTC compared to sporadic PTC (5-10), but this observation is not confirmed in all studies (14)(15)(16)(17)(18)(19)(20). There is even greater controversy to know whether the possible increased risk is due to the more aggressive initial presentation or whether a family history itself is an independent risk factor for recurrence (14).…”
Section: Discussionmentioning
confidence: 99%